Associations between dietary diversity score and migraine headaches: the results from a cross-sectional study - Amani Tirani, Shahnaz; Askari, Gholamreza; Khorvash, Fariborz; As’habi, Atefeh; Arab, Arman (Frontiers in Nutrition, 2023)
There is limited evidence on the link between diet quality and migraine headaches. The present study aimed to evaluate the association between dietary diversity score (DDS), as a good representative of overall diet quality, and clinical features of migraine headaches. In total, 262 subjects (224 females and 34 males), aged 20 to 50 years old were included in the present cross-sectional study. The migraine headache was diagnosed according to the third edition of the International Classification of Headache Disorders (ICHD-3). Clinical features of migraine headaches (frequency, severity, and duration of migraine headaches) headache impact test-6 (HIT-6), and serum level of nitric oxide (NO) were assessed by standard procedures. The dietary intake of participants has been assessed by a validated 168-item food frequency questionnaire (FFQ) and used to calculate DDS. The association between DDS and clinical variables of migraine headaches was investigated using multiple linear regression analysis, and the beta (β) estimates with 95 % confidence intervals (CIs) were reported. A significant inverse association was found between DDS and headache frequency (β= -2.19, 95% CI: -4.25, -0.14) and serum levels of NO (β= -6.60, 95% CI: -12.58, -0.34), when comparing patients in the third tertile of DDS to those in the first tertile. The association remained significant and became stronger after adjustment for confounders for both outcomes of headache frequency (β= -3.36, 95% CI: -5.88, -0.84) and serum levels of NO (β= -9.86, 95% CI: -18.17, -1.55). However, no significant association was found between DDS with HIT-6 score, migraine headache duration, and severity. The present study demonstrates that higher dietary diversity is correlated with lower migraine frequency and serum levels of NO.